2021
DOI: 10.1186/s12960-021-00559-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an mLearning application on nurses’ and midwives’ knowledge and skills for the management of postpartum hemorrhage and neonatal resuscitation: pre–post intervention study

Abstract: Background Globally, mobile learning (mLearning) tools have attracted considerable attention as a means of continuous training for healthcare workers. Rwanda like other low-resource settings with scarce in-service training opportunities requires innovative approaches that adapt technology to context to improve healthcare workers’ knowledge and skills. One such innovation is the safe delivery application (SDA), a smartphone mLearning application for Basic Emergency Obstetric and Neonatal Care (B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 34 publications
2
30
1
7
Order By: Relevance
“…This was a reflection about the baseline survey findings on the knowledge and skills in the management of PPH and NR, and on a 6 months’ record review of the BEmONC outcomes - Apgar score and PPH progressions. The survey results indicated that the average knowledge score was 47.2% and the average skills score was 59.9% among 33 midwives and 21 nurses interviewed for the survey [ 25 ]. The record review findings revealed an unstable newborn outcome (Apgar score < 7) following 10 min NR recorded in 62% ( n = 78) newborn cases and an unstable maternal outcome (persistent bleeding ≥500mls) following PPH management recorded in 19% ( n = 13) maternal cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a reflection about the baseline survey findings on the knowledge and skills in the management of PPH and NR, and on a 6 months’ record review of the BEmONC outcomes - Apgar score and PPH progressions. The survey results indicated that the average knowledge score was 47.2% and the average skills score was 59.9% among 33 midwives and 21 nurses interviewed for the survey [ 25 ]. The record review findings revealed an unstable newborn outcome (Apgar score < 7) following 10 min NR recorded in 62% ( n = 78) newborn cases and an unstable maternal outcome (persistent bleeding ≥500mls) following PPH management recorded in 19% ( n = 13) maternal cases.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this aspect of the study was to explore the participating nurses and midwives’ experiences and perceptions of obstetric care with a special focus on PPH management and NR. The objective of this aspect of the study was two-fold; one part was to elucidate from the participants’ explanations of the research findings [ 25 ] from the quantitative part of the research. The second part was to explore context specific factors that influence their work as obstetric care givers in their respective hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…This was a re ection about the baseline survey ndings on the knowledge and skills in the management of PPH and NR, and on a six months' record review of the BEmONC outcomes -Apgar score and PPH progressions. The survey results indicated that the average knowledge score was 47.2% and the average skills score was 59.9% among 54 nurses and midwives interviewed for the survey [23]. Nurses and midwives admitted to being surprised by the survey and record review results.…”
Section: Re Ections To Baseline Research Resultsmentioning
confidence: 95%
“…This was a re ection about the baseline survey ndings on the knowledge and skills in the management of PPH and NR, and on a six months' record review of the BEmONC outcomes -Apgar score and PPH progressions. The survey results indicated that the average knowledge score was 47.2% and the average skills score was 59.9% among 54 nurses and midwives interviewed for the survey [23]. The record review ndings revealed an unstable newborn outcome (Apgar score < 7) following 10 minutes NR recorded in 62% (n = 78) newborn cases and an unstable maternal outcome (persistent bleeding ≥ 500mls) following PPH management recorded in 19% (n = 13) maternal cases.…”
Section: Re Ections To Baseline Research Resultsmentioning
confidence: 96%
See 1 more Smart Citation